Invasive Bacterial Diseases in Northern Canada - Degani, Naushaba; Navarro, Christine; Deeks, Shelley L.; Lovgren, Marguerite; Canadian International Circumpolar Surveillance Working Group
International Circumpolar Surveillance (ICS) is a population-based invasive bacterial disease surveillance network. Participating Canadian regions include Yukon, Northwest Territories, Nunavut, and northern regions of Québec and Labrador (total population 132,956, 59% aboriginal). Clinical and demographic information were collected by using standardized surveillance forms. Bacterial isolates were forwarded to reference laboratories for confirmation and serotyping. After pneumococcal conjugate vaccine introduction, crude annual incidence rates of invasive Streptococcus pneumoniae decreased from 34.0/100,000 population (1999-2002) to 23.6/100,000 population (2003-2005); substantial reductions were shown among aboriginals. However, incidence rates of S. pneumoniae, Haemophilus influenzae, and group A streptococci were higher in aboriginal populations than in non-aboriginal populations. H. influenzae type b was rare; 52% of all H. influenzae cases were caused by type a. Data collected by ICS contribute to the understanding of the epidemiology of invasive bacterial diseases among northern populations, which assists in formulation of prevention and control strategies, including immunization recommendations.